Prostatic adenocarcinoma with a peculiar morphology - a rare case of pseudohyperplastic variant with inverted polarity - Daniel Abensur Athanazio; Maiara Ferreira de Souza; Maria Estela Pompeu do Amaral (BMC, 2022)
Abstract Background The inverted (hobnail) variant of high-grade prostatic intraepithelial neoplasia (HGPIN) has been reported in two previous series and one case of inverted polarity in invasive adenocarcinoma has been reported. We reported an additional case of invasive carcinoma with this peculiar morphology. Case presentation We reported an additional case of invasive carcinoma with this peculiar morphology. A prostatectomy specimen of a 64-year-old patient showed a GG2 adenocarcinoma with extensive intraprostatic perineural infiltration and extraprostatic extension. Half of the entire tumor showed a distinctive inverted morphology. Conclusion Although pseudohyperplastic adenocarcinoma is believed to be a low-grade tumor to be graded as Gleason pattern 3, awareness of this morphology is important to collect more information on its biologic behavior and clinical implication.